Family stature in idiopathic scoliosis. - Carr, A; Jefferson, R; Turner-Smith, A (1993)
The standing heights of 40 children with scoliosis and 110 persons from their immediate families were compared with those of a group of 349 contemporary control subjects. Skeletal bone ages and puberty ratings did not differ from normal, but the children with scoliosis were found to be significantly taller than the controls. They were also taller than their unaffected relatives, suggesting that the increased stature is not due to genetic factors alone. Scoliotic children with an affected immediate-family member were of normal height, which suggests that growth is of less etiological importance in children with a strong genetic susceptibility.